Literature citation and writer identity construction in linguistic academic discourse - Wan Liu; Yi Zhang (Heliyon, 2023)
This study revealed the distributional features of literature citation and writer identity in linguistic academic discourse, and further explored how writer identity is constructed through literature citation. Based on Petrić’s citation typology and Ivanič’s writer identity framework, the study investigated various types of citations and identities in thirty journal articles published in the Journal of English for Academic Purposes from 2017 to 2021. The results showed that there are a total of 1637 citation instances, among which the dominant type is attribution citation (36.59 %). Besides, the study revealed that 80.45 % of the total citations construct discoursal self only and 19.55 % reveal both discoursal self and authorial self. In terms of discoursal self, writers present themselves as a member of academic community, a contributor to a field of knowledge, a knowledgeable and professional scholar, and a reliable and credible writer. As for authorial self, they would like to position themselves to be a writer with authority and an evaluator. It is expected that the current study can help novice writers use citations strategically and establish their desired identity accordingly.